PEMBINAAN KEDISIPLINAN DAN KETERAMPILAN NARAPIDANA LEMBAGA PEMASYARAKATAN KELAS IIA PERMISAN NUSAKAMBANGAN (Unnes Civic Education Journal, 2022)
In prisons, prisoners not only serve their sentences and do nothing but they are given training and coaching. Prison is a place to provide guidance to prisoners and correctional students in Indonesia. The purposes of this study are 1) to determine the implementation of inmates' discipline and skill development activities, 2) prisoners' responses, and 3) the obstacles faced by the Correctional Institution in fostering the discipline and skills of prisoners. This study used a qualitative method carried out in Permisan Nusakambangan Prison. Methods of data collection in the form of: observation, interviews, and documentation. Test the validity of the data using triangulation. The data analysis technique is in the form of data collection, data reduction, data presentation and drawing conclusions or verification. The results of the study show that in general the disciplinary development in Permisan Prison follows the applicable rules. For the implementation of skill activities, there are hydroponics, batik, doormats, calligraphy, sewing, laundry and bakery. Inmates respond diligently and in a timely manner and follow the rules that apply in Permisan Prison as a whole. Obstacles in the process of developing discipline and skills, namely the location of prisons in remote areas and the access that must be taken in the form of land and sea, making it difficult to market products made by prisoners, as well as facilities and woodworking tools that need to be repaired and market expansion so that products from prisons known to the general public.